1995
DOI: 10.1007/s002770050088
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the p53 gene mutations in acute myelogenous leukemia: the p53 gene mutations associated with a deletion of chromosome 17

Abstract: In order to determine the relevance of the p53 tumor suppressor gene mutations in acute myelogenous leukemia (AML), we analyzed the p53 gene in genomic DNA of 18 unselected cases of AML by polymerase chain reaction-single-strand conformation polymorphism (PCR-SSCP) and direct sequencing. We detected three cases (16.7%) with the p53 gene mutations showing only the mutant alleles; the high incidence in cases with loss of a whole chromosome 17 (two of three) contrasted with the low incidence in cases without abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…We verified the previously reported homozygous nonsense P53 mutation at codon 196 in Hut-78 (R196Stop) (Ri et al, 2009) and identified a homozygous missense mutation at codon 245 (G245S) of exon 7 in SeAx cells at the DNA-binding domain ( Table 1). The G245S is a nonfunctional mutation located in the mutational hot spot region (exons 5-9) of P53 and is observed in several cancers including hematological malignancies (Hu et al, 1992;Wada et al, 1993;Kurosawa et al, 1995;Villuendas et al, 1997;Wong et al, 1999;Leroy et al, 2002;Wojcik et al, 2005). Although the G245S mutation disrupts the DNA-binding surface, the overall scaffold is retained when the protein is folded (Wong et al, 1999), explaining the observed stabilization of p53 after nutlin-3a.…”
Section: Expression and Mutation Status Of P53 In Ctcl Cellsmentioning
confidence: 95%
“…We verified the previously reported homozygous nonsense P53 mutation at codon 196 in Hut-78 (R196Stop) (Ri et al, 2009) and identified a homozygous missense mutation at codon 245 (G245S) of exon 7 in SeAx cells at the DNA-binding domain ( Table 1). The G245S is a nonfunctional mutation located in the mutational hot spot region (exons 5-9) of P53 and is observed in several cancers including hematological malignancies (Hu et al, 1992;Wada et al, 1993;Kurosawa et al, 1995;Villuendas et al, 1997;Wong et al, 1999;Leroy et al, 2002;Wojcik et al, 2005). Although the G245S mutation disrupts the DNA-binding surface, the overall scaffold is retained when the protein is folded (Wong et al, 1999), explaining the observed stabilization of p53 after nutlin-3a.…”
Section: Expression and Mutation Status Of P53 In Ctcl Cellsmentioning
confidence: 95%
“…7,13,15,19,32,33 Conversely, p53 mutations without cytogenetical alteration are a rare event. 32,33 In contrast, 10-30% of patients have a cytogenetical p53 deletion with wild-type configuration of the remaining allele.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,[13][14][15][16] However, in some cases the p53 deletion is present as a single chromosomal aberration and as a consequence treated in the standard risk group. So far, association of p53 mutations with poor overall survival (OS) has been described in AML, [17][18][19][20][21] but the prognostic impact of 17p aberrations in AML has been evaluated only in the context of complex aberrant karyotypes or other unfavorable cytogenetic markers. 5,6,16 Recently published data of 336 patients with AML including 9 patients with loss of 17p as sole abnormality revealed in vitro drug resistance and short OS in patients with 17p aberrations leading to p53 deletion.…”
Section: Introductionmentioning
confidence: 99%
“…It is less clear how tumor-suppressor genes complement other mutations in AML, but classical tumor-suppressor genes identified in AML include TP53 mutations in monosomy 17 AML (Fenaux et al, 1991;Kurosawa et al, 1995;Christiansen et al, 2001), RUNX1/ AML1 mutations in AML with chromosome 21 loss of heterozygosity (LOH) (Silva et al, 2003), and loss of the normal NF1 allele in children with neurofibromatosis type 1 and myeloid disorders including AML (Shannon et al, 1994).…”
Section: Introductionmentioning
confidence: 98%